Analysis of Scientific Literacy Capability in Aspects Attitude of Students in Yogyakarta - Syarifa Nurmarwaa; Jumadi; Heru Kuswanto (Jurnal Penelitian Pendidikan IPA, 2025)
One of the important qualities that students must possess is the ability to read and understand scientific texts. The ability and attitude of high school students' science literacy in Yogyakarta will be tested in this study. To provide a scientific explanation of what happens during data collection, this research uses a quantitative descriptive methodology. As many as sixty-six high school students from Yogyakarta were used as the research sample. The science literacy attitude aspect questionnaire was used as a direct data collection tool. Analysis, collecting literature, making instruments, presenting and reducing data, conclusion are some components of the data analysis method. In terms of the components of scientific literacy attitudes, the research found that high school students in Yogyakarta have a "enough" level of ability. Students' attitudes towards each component of scientific literacy skills are divided into three categories: "low" for honesty and critical thinking, "enough" for feeling of enthusiasm and collaborating, or "good" for perseverance and responsibility. Research findings indicate that high school students in Yogyakarta need to improve their scientific literacy skills, particularly in the attitude component. Ideas for better materials, appropriate learning media, and teaching models aligned with physics concepts are some of the efforts made to improve students' scientific literacy skills, which are still lacking in terms of attitude.